Titik Temu Zuhud dan Kawruh Begja: Studi Komparatif Al-Ghazali dan Ki Ageng Suryomentaram - Panji Nur Muhammad Sholih; Fathur Rozi (LPPI Universitas Al-Qolam Malang, 2025)
Amidst the wave of modernity characterized by the hegemony of materialism and technological disruption, modern humans face an acute existential crisis. The phenomena of alienation and spiritual emptiness have emerged as pervasive social pathologies. In Islam, Zuhud (asceticism/detachment) is proposed as a fundamental solution to overcome material dependency. However, the interpretation of Zuhud is frequently reduced to fatalism, structural poverty, and an anti-worldly stance, rendering it counterproductive to the spirit of contemporary progress. Conversely, the Nusantara archipelago possesses a repository of local wisdom known as Kawruh Jiwa or Kawruh Begja, initiated by Ki Ageng Suryomentaram, which offers a rationality of emotional processing. This study aims to conceptually reconstruct the meaning of Zuhud through the lens of Javanese indigenous psychology and to dissect the operational mechanism of